POSITIVE EXPERIENCE IN SOLVING ECONOMIC PROBLEMS OF COMMERCIAL BANKS ON INVESTING IN BONDS - V. Bobrova; E. Zolotova; E. Kalashnikova (Вестник Северо-Кавказского федерального университета, 2022)
BANKS ON INVESTING IN BONDS The banking system in the course of its activity acts as a complex dynamically developing system subject to a variety of different risks affecting the final results of the activities of a credit institution. One of the most important factors of the stability of the banking system and the least risky way of investing for a commercial bank is to attract bonds. This factor is closely related to the rapid development of the stock market. The article presents an analysis of the ruble corporate bond market for investment by commercial banks and risk minimization. At the same time, the average modified duration was calculated by sectors of the economy. The bonds were ranked according to various criteria, by sectors of the economy, and by reliability. The results ofthe analysis of various methods for determining the riskiness of bonds are presented. The conclusion about the influence of the key rate on the price of bonds is given. The effectiveness ofprotect the portfolio of a commercial bank from.